Biology of Two Indian Bamboos, their Culm Potential and Problems of Cultivation - Kondas, S. (Indian Forester, 1982)
The two most important bamboos of India are Dendrocaldmus strictus and Bambusa arundinacea. Management of bamboo plantations presupposes a good knowledge of rhizome and culm biology. Both the above species are pachymorph type. Their culm growth and development depend upon rhizome size and position. There appears to be a growth periodicity consisting of a growth phase lasting 150-180 day, which commences with the rains in June-July-August and a biological consolidation phase for the remaining six months. This cycle goes on repeating. Though both the bamboos record sporadic flwering almost every year, they seed profusely in drier situations. In moist situations, it is not uncommon that seeding does not necessarilly follow flowering. Observations on Bambusa arundinacea show that it can be succesfully selfed and the seeds are fertile. An attempt is made to project the yield on the assumption that in a stabilised clump the culm potential varies from one to two for each of the current rhizomes which average at 1.5. A hectare may contain a growing stock of 4000 to 5000 culms (250 to 300 clumps) and provide an annual cut of 750 to 1000 culms on a three year felling cycle. There are several phenotypes available in nature with regard to stature, branchiness, hollowness of culm, etc and the possibility of selecting useful types is strong as both the species are sub-continental in distribution. The problems of cultivation relate to moisture conservation, plant protection and continuous tendirg. The avenues of research relate to seed viabilty, polymorphism, rhizome biology and cloning by tissue culture.